ANALISIS FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PARTISIPASI PEREMPUAN UNTUK BEKERJA DI KOTA BEKASI - Zalsabila (2023)
Bekasi City is the city with the most population in West Java Province with a sizable sex ratio of 101. Based on classical economic growth theory, population growth is one of the main factors that support economic growth, however this does not happen in Bekasi City. Bekasi City, which is the city with the largest population in West Java Province, does not make Bekasi City superior in economic growth. One of the things that causes economic growth in Bekasi City to be lower than other cities in West Java Province is the lack of contribution of women in working in Bekasi City. This study aims to determine the social and economic factors that encourage women's participation to work in Bekasi City and to look at the problems and key variables that can support women to work. In this study, the analysis used continuous analysis techniques which were processed using MicMac software. The results obtained in this study 1) economic factors directly or indirectly are still the main factors that encourage women's participation in work 2) social factors are not the main factors that encourage women's participation in work in Bekasi City, but social factors cannot ignored because it indirectly has a big influence on women's participation to work in Bekasi City. Indicators of social factors that have a strong influence on women's participation to work in Bekasi City include marital status, self-existence and education level.